The Influence of Motivation and Knowledge on Readiness to Take Risks in Entrepreneurship Processes - Ariyono Setiawan (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
This research analyzes the influence of intrinsic motivation, extrinsic motivation, market knowledge, and technological knowledge on individuals' readiness to face risk in the context of entrepreneurship. Through regression and ANOVA analysis approaches, this study aims to identify factors contributing to individuals' attitudes and behaviors in confronting challenges in entrepreneurial endeavors. The results of the Model Summary analysis indicate that intrinsic and extrinsic motivation significantly impact readiness to face risk, while market and technological knowledge also positively relate to a proactive attitude toward risk. The implications of these findings are relevant for policy development and focused entrepreneurship education. This research provides a deeper insight into the factors influencing individuals' preparedness to face risk in the entrepreneurial world, forming the basis for efforts to foster a dynamic and innovative entrepreneurial culture within society.